Secular stagnation and progressive economic policy alternatives - Özlem Onaran (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2016)
This paper summarizes two main findings in the post-Keynesian literature regarding the linkages between financialization, income distribution, accumulation and productivity. First, at the core of secular stagnation lies the missing link between profits and investment. Second, rising inequality and financialization have been the main reasons for this missing link and hence the major brakes against capital accumulation and growth. The paper concludes with alternative progressive policies based on a coordinated policy mix of equality-led development and public investment.
Keywords: E12; E22; E25; 330; wage share; wage-led growth; globalization; public investment